Effects of Botrytis cinerea and Erysiphe necator fungi on the aroma character of grape must: A comparative approach - Lopez Pinar, Angela; Rauhut, Doris; Ruehl, Ernst; Büttner, Andrea (Food Chemistry, 2016)
Botrytis cinerea and Erysiphe necator are among the most relevant fungi in viticulture. In order to deepen our knowledge about their potential impact on wine quality, their effects on the aroma character of the initial stage of wine production, i.e. the must were studied. The main aroma compounds were determined by gas chromatography–olfactometry (GC-O) and ranked according to their relative intensities by means of aroma extract dilution analysis (AEDA). Clear differences between healthy and infected samples were observed. Botrytis cinerea had a positive impact on fruity and floral notes while several earthy smelling compounds were developed as result of the infection. Unlike in previous studies, however, we did not observe any clear differences in the quantities of earthy-mushroom-like smelling substances as result of the infection process with Erysiphe necator</em
Keywords: Must; Botrytis cinerea; Erysiphe necator; gas chromatography-olfactometry (GC-O)